2016
DOI: 10.1097/hcr.0000000000000170
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of Exercise Self-efficacy in a Randomized Trial of Mind-Body Exercise in Patients With Chronic Heart Failure

Abstract: Purpose Exercise self-efficacy is one of the strongest predictors of physical activity behavior. Prior literature suggests that tai chi, a mind-body exercise, may increase self-efficacy, however this is not well-studied. Little is known about the factors associated with development of exercise self-efficacy in a heart failure population. Methods We utilized data from a randomized controlled trial of 12 weeks group tai chi classes vs. education in patients with chronic heart failure (N=100). We used multivari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
34
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(36 citation statements)
references
References 33 publications
1
34
0
1
Order By: Relevance
“…Figure 1 presents all the articles that were selected for this systematic review. Of the 37 articles reviewed focused on clarifying the relationship between fitness parameters and exercise self-efficacy, 32 articles were focused on populations with some type of pathology [ 6 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 ]. Five articles focused on the pathology-free middle-aged population [ 62 , 63 , 64 , 65 , 66 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Figure 1 presents all the articles that were selected for this systematic review. Of the 37 articles reviewed focused on clarifying the relationship between fitness parameters and exercise self-efficacy, 32 articles were focused on populations with some type of pathology [ 6 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 ]. Five articles focused on the pathology-free middle-aged population [ 62 , 63 , 64 , 65 , 66 ].…”
Section: Resultsmentioning
confidence: 99%
“…On 24 occasions, the test used was “The 6-Min Walk Test” (6MWT) that assesses aerobic endurance Self-perceived physical fitness was assessed on 14 occasions [ 6 , 34 , 37 , 39 , 40 , 43 , 47 , 53 , 56 , 58 , 59 , 61 , 65 , 66 ]. “The Foot Up and Go” test was used on six occasions [ 34 , 42 , 48 , 54 , 55 , 62 ]; “The Sit to Stand Test” [ 34 , 39 , 46 , 57 , 61 , 62 ]; “The Handgrip forced test” was used to evaluate the strength of the upper and lower body, agility in the face of possible falls, flexibility of the upper and lower body, and dynamic balance [ 39 , 42 , 46 , 57 , 61 , 63 ]. In five occasions “Treadmill Test” was used [ 6 , 45 , 60 , 63 , 64 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, an analysis of data from a randomized controlled trial of tai chi for patients with heart failure has shown that increases in exercise selfefficacy mediated changes in functional status. 52 To our knowledge, this is the first study that examined the effect of tai chi on objectively assessed PA among patients not attending CR. One study conducted in outpatients with class I to III systolic heart failure found that participation in a 12-week tai chi training program improved self-reported PA (CHAMPS (Community Healthy Activities Model Program for Seniors/CHAMPS activities questionnaire)) compared with controls.…”
Section: Discussionmentioning
confidence: 94%
“…As a result, participants do not see tai chi exercise as threatening, and this may result in improvements in exercise self‐efficacy. In fact, an analysis of data from a randomized controlled trial of tai chi for patients with heart failure has shown that increases in exercise self‐efficacy mediated changes in functional status …”
Section: Discussionmentioning
confidence: 99%